HAM DALAM TERMINOLOGI DOKTRIN HUKUM ISLAM (Penelaahan Ayat dalam al-Qur’an dengan Tafsir Maudhu’iy) - BUDIARTI A. RAHMAN (LPPM IAIN Parepare, 2014)
This study discusses about the basic concepts and forms of Human Rights in the Koran as the basic source of Islamic law since the beginning of its discussion until today. The forms of human rights in the Koran, such as freedom, equality, and justice, seems clear that Islamic law have a strong foundation in matters of human rights. Even in the particular context, the human rights in Islam in advance of the Western version. Islamic law very confesses of human rights as basic rights and puts it as primary need.